2023
DOI: 10.1037/emo0001230
|View full text |Cite
|
Sign up to set email alerts
|

The longest year ever: Emotions and time perception interact to predict how frequently individuals engage in COVID-19 avoidance behaviors.

Abstract: Affective states alter the perception of how quickly time is passing. However, previous studies have not examined the independent and interactive effects of emotion and time perception on behavioral outcomes. The current study sought to better understand the relationships between affect, time perception, and reported engagement in COVID-19 pathogen avoidance behaviors (e.g., social distancing, wearing a mask) over 1 year. The study sample was comprised of American adults (n = 1,000) recruited using Prolific. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 40 publications
0
1
0
1
Order By: Relevance
“…Thus, when people are fearful of COVID-19, they may show avoidance behaviors such as reducing use of public transportation, wearing masks or reducing mobility (Ito et al, 2022) in order to inhibit the spread of infectious diseases. In addition, recent research has shown that avoidance-based affective states are associated with stricter adherence to health behaviors (Wendel and Gable, 2023). On the basis of their fear of COVID-19, people are more inclined to wear masks to avoid infection.…”
Section: Avoidancementioning
confidence: 99%
“…Thus, when people are fearful of COVID-19, they may show avoidance behaviors such as reducing use of public transportation, wearing masks or reducing mobility (Ito et al, 2022) in order to inhibit the spread of infectious diseases. In addition, recent research has shown that avoidance-based affective states are associated with stricter adherence to health behaviors (Wendel and Gable, 2023). On the basis of their fear of COVID-19, people are more inclined to wear masks to avoid infection.…”
Section: Avoidancementioning
confidence: 99%
“…Os estados emocionais estão intimamente ligados à percepção do tempo, ou à experiência subjetiva de quão rápido o tempo está passando (Droit-Volet & Gil, 2009;Wendel & Gable, 2023).…”
Section: Introductionunclassified